PARTISIPASI MASYARAKAT DALAM PEMBANGUNAN DEMPLOT AGROFORESTRI JAMBLANG (Syzygium cumini Linn) (Community participation in the development demplot agroforestry of Jamblang (Syzygium cumini Linn)) - maria palmolina (Jurnal Agroforestri Indonesia, 2019)
The aim of this study was to describe the community participation in the development of jamblang based agroforestry demonstration plot (demplot) . The results of this study can be used as one of the references in the implementation of other forestry development. The method used was a descriptive research method with a qualitative approach. The research was carried out from 2015 to 2019, in Batu Dua, Linggajaya Village. The results of the study showed that the process of development demplot agroforestry of jamblang did not run partially, but was an integrated until between community participation and the construction of the development demplot  agroforestry of jamblang; from the start of activities (planning), implementation, supervision / evaluation, to beneficiaries. Both the BPPTA research team and the farmers involved in the development demplot agroforestry of jamblang looked at each other as actors and beneficiaries of development.